An emerging research ethos 1998–2004 A case study from a merger in teacher education in Iceland - Macdonald, Allyson (Menntavísindasvið Háskóla Íslands, 2016)
The aim of this case study is to identify factors that influenced the research culture and the emerging research ethos in the Iceland University of Education (IUE) during the years 1998–2004. The IUE was formed in 1998 when four organizations merged, only one of which had staff with a salaried responsibility for research prior to the merger. The study analyses published documents, as well as summaries of research activity and other information, collected between 1998–2004, in order to describe internal assimilation and external adaptation, as well as interactions between the two. Artefacts, basic assumptions and espoused values underpin the emergence of the culture (Schein, 2010). Attempts were made to strengthen the research infrastructure in the institution as staff members grappled with the need to engage in discovery, the scholarly activity defined by Boyer (1990) to be most like research. The IUE was characterized by new management structures, as well as provision of support and incentives. Staff motives for carrying out research influenced and were influenced by internal developments. The organizational culture was affect ed also by the external research environment, especially the changing research structures at the larger University of Iceland (UI) and changes in national research policy in science and technology. The interaction between assimilation and adaptation is apparent in the request for a national evaluation of educational research and in the development of research policy documents. There was some conflict between the tendency of staff to work on integration and application, as defined by Boyer (1990), and the external pressure to further develop discovery as a scholarly activity. The conflict arose in part because many of the staff were serviceoriented in their work but the form of discovery dominating the external environment was oriented towards pure rather than applied research. The ethos of research activity was one of cautious optimisim about the value of research and growing ...